2022
DOI: 10.21203/rs.3.rs-1074713/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis of spleen in chickens administered β-glucan derived from yeast cell wall

Abstract: Background Our previous study shown that oral administration of a product contained yeast cell wall polysaccharides enhanced immune responses elicited by Newcastle disease virus and changed microbial community of cecum in chickens. Results The present study was design to investigate the potential molecular mechanism in relation to the immunomodulation of β-glucan in chickens. Using RNA-sequence (RNA-seq) technique, we identified 198 differential expression genes (DEGs) in spleen in chickens after oral admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…3.81 ± 0.64 For Immune Globulins, the blood serum IgG concentration of rats after 15 days of treatment and after 30 days of treatment showed that treatment group 6 was the highest group that meets the results of the negative control group, and diagrams (1) and (2) clears this result and means that when the concentration of B glucan in feed was 25 mg/kg of feed, that was the ideal concentration for IgG to have an effect in the blood. Cao et al (2022) found that the Immunomodulatory effect of polysaccharides from yeast cell walls has been demonstrated effective to change immune response and altered gut microbiota composition in chickens. In our previous study, a yeast cell wall product containing β-glucan and MOS was found effectively to enhance intestinal IgA response to NDV vaccination and modulated the cecum microbiota by oral route.…”
Section: Chromosomal Aberration Testmentioning
confidence: 99%
“…3.81 ± 0.64 For Immune Globulins, the blood serum IgG concentration of rats after 15 days of treatment and after 30 days of treatment showed that treatment group 6 was the highest group that meets the results of the negative control group, and diagrams (1) and (2) clears this result and means that when the concentration of B glucan in feed was 25 mg/kg of feed, that was the ideal concentration for IgG to have an effect in the blood. Cao et al (2022) found that the Immunomodulatory effect of polysaccharides from yeast cell walls has been demonstrated effective to change immune response and altered gut microbiota composition in chickens. In our previous study, a yeast cell wall product containing β-glucan and MOS was found effectively to enhance intestinal IgA response to NDV vaccination and modulated the cecum microbiota by oral route.…”
Section: Chromosomal Aberration Testmentioning
confidence: 99%